Rotavirus genotypes associated with childhood severe acute diarrhoea in southern Ghana: a cross-sectional study - Enweronu-Laryea, C.C.; Sagoe, K.W; Damanka, S.; Lartey, B.; Armah, G.E. (My University, 2013)
Abstract Background Rotavirus immunization has been effective in developed countries where genotype G1P[8] is the predominant rotavirus strain. Knowledge of circulating strains in a population before introduction of rotavirus immunization program will be useful in evaluating the effect of the intervention. Methods Rotavirus was identified by enzyme immuno-assay (EIA) on stool specimens of children (age 0 – 59 months) hospitalized with acute gastroenteritis from August 2007 to February 2011 in Accra, Ghana. Rotavirus positive specimens were further characterized by polyacrylamide gel electrophoresis (PAGE) and reverse-transcriptase polymerase chain reaction (RT-PCR). Results Of the 2277 acute gastroenteritis hospitalizations 1099 (48.2%) were rotavirus-positive by EIA. Of the 1099 cases 977 (89%) were PAGE positive. All EIA positive specimens were further subjected to RT-PCR and 876 (79.7%) had sufficient material for characterization. Of these 876 cases, 741 (84.6%) were assigned G genotype, 709 (80.9%) P genotype, and 624 (71.2%) both G and P genotypes. We identified 8 G genotypes (G1, G2, G3, G4, G8, G9, G10, G12) and 3 P genotypes (P[4], P[6], P[8]). G1 (50.9%), G2 (18.8%), G3 (12.8%), P[8] (36.1%) and P[6] (30.7%) were the most prevalent. The most prevalent genotype combination was G1P[8] (28%). Mixed G (7.3%) and P (24.2%) genotypes were not uncommon. There was year-by-year and seasonal variations for most genotypes. Conclusion There is great diversity of rotavirus strains in children with severe gastroenteritis in southern Ghana. Even though cross-protection with vaccine-induced immunity occurs, continued strain surveillance is recommended after the introduction of rotavirus vaccine in the national immunization program.